Relationship between Energy and Economic Growth: Evidence from a Panel Nonlinear ARDL Model - Belloumi, Mounir; Aljazea, Ahmed (International Journal of Energy Economics and Policy, 2024)
In this article, we study the heterogeneous relationship among energy consumption and economic growth by incorporation gross fixed capital formation, foreign direct investment, international trade and finance development as control variables in a selected sample of 11 countries of the Middle East and North Africa over the period 1980-2020 using a panel nonlinear autoregressive distributed lag model. Empirical results show the presence of an asymmetric long run relationship between energy consumption and economic growth in the group of countries. The Pooled Mean Group estimates indicate that positive and negative changes in energy consumption have positive and significant effects on output growth in the long term, whereas both Mean Group and Difference Fixed Effect estimates report that only negative changes in energy consumption have positive and significant effect on long-term economic growth in the selected sample of countries. In addition, the short run individual effects of energy use on economic growth are positive and significant for only three countries (Jordan, Saudi Arabia, and Tunisia). These results are very important for the design of energy policies and sustainable economic growth. Energy-saving policies are suitable for long-run economic growth for the entire sample, while they are only suitable for eight countries out of eleven in the short-run.